Fatores associados ao nível de atividade física em indivíduos com doença de Parkinson durante o período de pandemia de COVID-19: um estudo transversal - Alencar, Madeleine Sales de (2022)
Individuals with Parkinson's disease (PD) tend to be more inactive than those without this condition. Social restriction measures during the COVID-19 pandemic may have aggravated the physical inactivity of this population, which may have led to a worsening of their physical conditioning and decreased their functional capacity. In addition, the changes in lifestyle and circadian cycle caused by social restrictive measures may also have had a negative impact on sleep quality and generated daytime sleepiness in individuals with PD who already have a greater predisposition to sleep disorders due to their base condition. Studies that assess the health of individuals with PD during the period of the pandemic are of great relevance due to the possibility of many negative impacts of this period of established social isolation. The diverse cinical manifestations arising from PD associated with social resctriction can interfere with the performance of different activities and social roles of individuals with PD. This study aims to identify factors associated with the level of physical activity and assess sleep quality and daytime sleepiness in individuals with PD during the COVID-19 pandemic. Methods: From May to December 2020, this cross-sectional and observational study collected data on the first teleconsultations of individuals with PD in follow-up at a movement disorder specialized outpatient clinic. Teleconsultations were instituted because of the COVID-19 social restriction. During data collection, the short version of the International Physical Activity Questionnaire (IPAQ), the Pittsburg sleep quality index, the Epworth sleepiness scales, and the Schwab and England clinical assessment were used. Mann-Whitney U test, Student's t test and Poisson regression were used for statistical analysis. Results and discussion: Higher functional capacity, assessed by the Schwab and England scale, and absence of sleep disorder were associated with a higher level of physical activity in PD. Sedentary and irregularly active individuals constituted 61.9% of the population studied, thus, seeking ways to increase physical activity levels in this population is important due to this high prevalence. Conclusion: The present study showed that higher levels of functional capacity and absence of sleep disorders were associated with better levels of physical activity in individuals with PD, emphasizing the importance of pharmacological and non-pharmacological therapies for better health conditions, especially in periods of social restriction.